The emotional-psychological consequences of infertility among infertile women seeking treatment: Results of a qualitative study - Hasanpoor-Azghdy, Seyede Batool (Research and Clinical Center for Infertility, 2014)
Background: Infertility is a major life event that brings about social and psychological problems. The type and rate these problems in the context of socio-cultural of different geographical areas and sex of people is different. Objective: The aim of this qualitative study was to explain the psychological consequences of infertility in Iranian infertile women seeking treatment. Materials and Methods: This qualitative study was done using qualitative content analysis on 25 women affected by primary and secondary infertility with no surviving children in 2012. They were purposefully selected with maximum sample variation from a large Fertility Health Research Center in Tehran, Iran. Data were collected using 32 semi-structured interviews and analyzed by the conventional content analysis method. Results: The findings of this study include four main themes: 1. Cognitive reactions of infertility (mental engagement; psychological turmoil). 2. Cognitive reactions to therapy process (psychological turmoil; being difficult to control in some situations; reduced self-esteem; feelings of failure). 3. Emotional-affective reactions of infertility (fear, anxiety and worry; loneliness and guilt; grief and depression; regret). 4. Emotional-affective reactions to therapy process (fear, anxiety and worry; fatigue and helplessness; grief and depression; hopelessness). Conclusion: This study revealed that Iranian infertile women seeking treatment face several psychological-emotional problems with devastating effects on the mental health and well-being of the infertile individuals and couples, while the infertility is often treated as a biomedical issue in Iranian context with less attention on the mental-emotional, social and cultural aspects. This article extracted from Ph.D. thesis. (Seyede Batool Hasanpoor-Azghady)